Pembinaan Warga Gereja dan Keluarga terhadap Anak dalam Membentuk Iman dan Berkarakter Kristiani - Febi Finensya Tambunan; Jelita Marsyah Sinaga; Mickael Ria Elisabet Bancin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper investigates various forms of church training for children, highlighting the central role of the family as the primary foundation. Based on a theological interpretation of Job 5:18 and an understanding of the family as a